Penggunaan Smartboard Mendorong Pembelajaran Kolaboratif dan Kreativitas Siswa Gen Alpha Sekolah Dasar di Era Digital: Penelitian - Suryani; Atania Rosbina Br Bangun (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The purpose of this study is to assess the influence and implementation process of Smartboard in encouraging collaborative learning and creativity of Generation Alpha students in elementary schools in the digital era. Generation Alpha or also known as generation Y is a group of children born after 2010. They have the character of being digital natives, familiar with gadgets and like to access the internet but also often distorted and lack social interaction, The reason for this study is that Gen Alpha requires a different educational approach. This research method uses a mixed method sequential explanatory, starting with a quantitative stage of quasi-experiment (experimental and control classes) and then qualitative methods through observation and interviews at SDS Kemala Bhayangkari 01 Medan. The research instruments used were a collaboration questionnaire, a product creativity test, observation guidelines, and interviews. Quantitative results showed a significant increase in the experimental class for collaboration scores (p<0.01) and creativity (p<0.05). Qualitative findings revealed three main themes: (1) the transformation of students' roles from passive to active collaboration through digital and multi-touch group workspaces, (2) stimulation of creativity through visuals, audio, and gamification, and (3) lively classroom dynamics with multi-directional communication. The combined results indicated that the Smartboard acted as a catalyst that facilitated a participatory learning environment, fostering 21st-century skills. This study suggests ongoing teacher training, curriculum-based content integration, and systematic evaluation for optimizing educational technology investments.